PTU-003 Circulating levels of Interleukin-18 correlate with severity following human acute liver injury. (28th May 2012) - Craig, D G; Conway-Morris, A; Lee, P; Pryde, A; Simpson, J; Hayes, P C; Simpson, K J
Abstract : Introduction: Excessive innate immune activation may precipitate multiorgan failure following paracetamol overdose (POD). Identification of amplification loops in this process could reveal novel therapeutic targets. Interleukin (IL)-18 is a potent proinflammatory cytokine which stimulates downstream T helper-1 cell responses and may trigger loss of regulatory natural killer (NK) cells. Methods: Consecutive patients (n=46, (19 (41.3%) male) admitted to the Royal Infirmary of Edinburgh with paracetamol-induced acute liver injury (ALT>1000 IU/l and coagulopathy) were enrolled. IL-18 levels were measured by ELISA. Immunophenotypic analysis of circulating lymphocytes was determined in whole blood by fluorescence-activated cell sorter (FACS) analysis. Results: A total of 29/46 (63.0%) PODs developed hepatic encephalopathy (HE), and therefore acute liver failure. IL-18 levels were significantly higher in PODs (median 457 (IQR 340–671) pg/mL, n=46) compared with chronic liver disease (292 (192–591) pg/ml, n=15, p<0.05) and healthy (163 (90–191) pg/ml, n=13, p<0.001) controls. Admission IL-18 levels in PODs correlated with both pro- and anti-inflammatory cytokines such as IL-6 (Spearman's r=0.491, p=0.001) and IL-10 (r=0.360, p=0.019), with markers of T-cell (IL2-sRα, r=0.567, p<0.0001) and macrophage (neopterin, r=0.422, p=0.015) activation, and with organ failure scores (SOFA, r=0.485, p=0.0007; APACHE II, r=0.466, p=0.001). Admission IL-18 levels were significantly higher in PODs who developed HE (p=0.0006) or the systemic inflammatory response syndrome (p=0.038), and in PODs who died/required emergency liver transplantation (OLT, p=0.020; AUC 71.4% (95% CI 55.4% to 87.4%). Flow cytometry analysis of peripheral blood lymphocytes revealed a significant decrease in the proportion of CD3-/CD56+ NK cells, with rapid recovery following OLT. Conclusion: IL-18 is associated with innate immune activation and adverse outcomes following POD. Future animal studies should explore IL-18 and NK cell modulation following POD. Competing interests: None declared.